Performance Comparison Between HMLP, MLP And Recurrent Networks With Applications To Carbon Monoxide Concentrations Forecasting. - Raji, Usharani; Mashor, M.Y.; Adom, A.H.; Ali, A.N; Sadullah, A.F. (2005)

(untitled)
This paper compares the performance of Hybrid Multilayered Perceptron (HMLP) network, Multilayered Perceptron (MLP) network and Recurrent network. These networks are used to model and forecast carbon monoxide (CO) concentration.